Central blood pressure and pulse wave velocity: relationship to target organ damage and cardiovascular morbidity-mortality in diabetic patients or metabolic syndrome. An observational prospective study. LOD-DIABETES study protocol - Castaño-Sánchez Carmen; Rodríguez-Martín Carmela; Sánchez-Salgado Benigna; de Cabo-Laso Angela; Castaño-Sánchez Yolanda; Rodríguez-Sánchez Emiliano; Recio-Rodríguez José I; Gómez-Marcos Manuel A; Gómez-Sánchez Leticia; García-Ortiz Luis (BMC, 2010)
Abstract Background Diabetic patients show an increased prevalence of non-dipping arterial pressure pattern, target organ damage and elevated arterial stiffness. These alterations are associated with increased cardiovascular risk. The objectives of this study are the following: to evaluate the prognostic value of central arterial pressure and pulse wave velocity in relation to the incidence and outcome of target organ damage and the appearance of cardiovascular episodes (cardiovascular mortality, myocardial infarction, chest pain and stroke) in patients with type 2 diabetes mellitus or metabolic syndrome. Methods/Design Design: This is an observational prospective study with 5 years duration, of which the first year corresponds to patient inclusion and initial evaluation, and the remaining four years to follow-up. Setting: The study will be carried out in the urban primary care setting. Study population: Consecutive sampling will be used to include patients diagnosed with type 2 diabetes between 20-80 years of age. A total of 110 patients meeting all the inclusion criteria and none of the exclusion criteria will be included. Measurements: Patient age and sex, family and personal history of cardiovascular disease, and cardiovascular risk factors. Height, weight, heart rate and abdominal circumference. Laboratory tests: hemoglobin, lipid profile, creatinine, microalbuminuria, glomerular filtration rate, blood glucose, glycosylated hemoglobin, blood insulin, fibrinogen and high sensitivity C-reactive protein. Clinical and 24-hour ambulatory (home) blood pressure monitoring and self-measured blood pressure. Common carotid artery ultrasound for the determination of mean carotid intima-media thickness. Electrocardiogram for assessing left ventricular hypertrophy. Ankle-brachial index. Retinal vascular study based on funduscopy with non-mydriatic retinography and evaluation of pulse wave morphology and pulse wave velocity using the SphygmoCor system. The medication used for diabetes, arterial hypertension and hyperlipidemia will be registered, together with antiplatelet drugs. Discussion The results of this study will help to know and quantify the prognostic value of central arterial pressure and pulse wave velocity in relation to the evolution of the subclinical target organ damage markers and the possible incidence of cardiovascular events in patients with type 2 diabetes mellitus. Trial Registration ClinicalTrials.gov Identifier: NCT01065155